Using Measures of Agreement to Evaluate a Chronic Problem of Congestion in the Empty Container Depots - Zain, Rosmaizura Mohd; Rahman, Mohd Nizam Ab.; Ramli, Ainon; Nopiah, Zulkifli Mohd; Saibani, Nizaroyani (International Review of Management and Marketing, 2016)
Container-based transportation through a combination of truck, rail and ocean shipping services has become an important part of supporting local and international cargo flows. However, congestion or bottlenecks of empty container-trucks may hinder the supply chain and logistics performance of the country in hinterland transport. The factors causing the bottlenecks of empty container-trucks at the depots around Port Klang, Malaysia, were first derived from interviews conducted with 30 participants working in different logistics companies. This paper intends to describe the application of Fleiss kappa to evaluate or validate the congestion factors and involves six experienced evaluators from the field of empty container logistics. Therefore, key steps and procedures are presented by extracting the qualitative data from a previous study that addressed this phenomenon. A resulting Fleiss generalised kappa value of 0.8203, which can be assumed as satisfactory and reflecting the strength of the congestion factors, as well as it demonstrated the real situation. Truly, Fleiss kappa has proved to be an efficient and useful approach to measure the agreements for many purposes, including validating the chronic congestion factors. Keywords: Interrater Agreement; Congestion; Empty Container-Truck JEL Classifications: L90, L91, L92